The architecture and use of social media in the 2015 Nigerian general elections (2016)
This paper analyses the use of social media for political mobilisation and communication during the 2015 General Elections in Nigeria. Its aim is to describe the structure and context of information dissemination and communication among political actors, agents and the electorate during this period. It argues that the widespread use of social media was due to the evolving technological architecture of the Internet as well as the ready supply of human technical competencies and appetite for use. The technical setting for the observed level of use depended on several factors, which included, primarily, high Nigerian mobile teledensity, a relatively large number of Internet service providers, a demographic youth bulge and real time communication. It was facilitated by improvements in the availability, accessibility, affordability, and adaptability of the Internet and mobile phones. These factors, among others, were the precursors and enhancers of political communication via social media during the elections.